Implementation of the business model canvas in designing business development strategies for Loush Bath MSME - Marliani, Ismawati Putri; Gandhy, Abel; Prasetyo, Bayu Dwi (Jurnal Mantik, 2025)
The growth of the natural soap industry in Indonesia encourages Micro, Small, and Medium Enterprises (MSMEs) to design sustainable and adaptive business strategies. Loush Bath, an MSME in Bogor, produces natural exfoliating soap made from soap nuts, loofah, and orange peel, which is the subject of this research. This study focuses on the application of the Business Model Canvas to illustrate how to create, deliver, and capture business value (BMC) in designing Loush Bath's business development strategy, which aligns with the increasing consumer trend towards environmentally friendly and ethically sourced products. The primary objective of this research is to understand the nine elements of BMC about the current business situation and to identify strengths and areas for improvement. The method employed was a descriptive qualitative approach, utilizing data collection techniques that included semi-structured interviews, direct observation, and internal documentation. Data analysis was done thematically based on the BMC framework. The results showed that Loush Bath has effectively implemented most of the BMC elements, especially in value proposition, customer relationships, and digital distribution channels. However, challenges still exist, such as the lack of product diversification and the absence of a structured financial recording system. The conclusion of this study states that the application of BMC can provide a systematic, contextual, and responsive strategic framework for natural product-based MSMEs. Recommendations include product diversification, financial digitalization, optimizing digital distribution, strengthening local partnerships, and ensuring product legality.